2016
DOI: 10.1590/1807-55092016000100097
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic variables of table vault on artistic gymnastics

Abstract: The table vault is an event of male and female Artistics Gymnastics. Although it can be performed in a variety of rotations and body positions in different phases, it can be separated in three groups: handspring, Yurchenko and Tsukahara. It is believed that kinematic variables of vault may vary according to group of vault or gymnast body position, but few studies compares the real differences among the three groups of vaults, comparing and describing the variables in different phases. Vault kinematic variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(76 reference statements)
2
5
0
Order By: Relevance
“…We observe a significant lower score for cluster three on second phase and for clusters one and two during the fourth phase, confirming that, at least for the variables considered, the range for variability of movement prototypes are reduced. During both phases, gymnasts body position [ 42 ], specially hip flexion/extension angles [ 36 ], velocity and force applied to mini trampoline and vaulting table are crucial for success [ 36 , 39 ], which corroborates the strong associations with score that we found. Despite the short duration of hands contact with vaulting table, it is possible that elite gymnasts make small modifications in linear and angular momentum to improve the distance, height and body rotation during the second flight [ 43 ] (phases five and six, between vaulting table take-off and landing).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We observe a significant lower score for cluster three on second phase and for clusters one and two during the fourth phase, confirming that, at least for the variables considered, the range for variability of movement prototypes are reduced. During both phases, gymnasts body position [ 42 ], specially hip flexion/extension angles [ 36 ], velocity and force applied to mini trampoline and vaulting table are crucial for success [ 36 , 39 ], which corroborates the strong associations with score that we found. Despite the short duration of hands contact with vaulting table, it is possible that elite gymnasts make small modifications in linear and angular momentum to improve the distance, height and body rotation during the second flight [ 43 ] (phases five and six, between vaulting table take-off and landing).…”
Section: Discussionsupporting
confidence: 82%
“…The numbers of clusters allocated to the six phases of movement show that a diversification of movement prototypes is more likely to occur along some phases, which is moderately associated with movement variability. Results showed that statistically significant differences for scores occurred for movement during phases one, two, four and six, confirming the significant correlations of these phases with judges’ scores [ 4 , 34 , 35 , 36 ], while phases three and five have less influence on scores, showing a similar range of scores for all clusters.…”
Section: Discussionsupporting
confidence: 53%
“…Take-off velocity did not differ across groups, but all participants demonstrated greater take-off velocity during the MTVT (see Table 2 ), highlighting that motor behaviour is influenced by task constraints. As we predicted, greater velocities during the approach run and take-off have been shown to be associated with better performances and higher scores on vaulting [ 19 , 21 , 22 , 37 ]. The higher level of complexity on the MTVT task likely explains this discrepancy in take-off velocities between apparatuses [ 20 , 37 ].…”
Section: Discussionmentioning
confidence: 83%
“…From a technical point of view, MTVT skills present additional constraints specifically during the first flight phase (i.e., from mini-trampoline to vaulting table) and the second flight phase (i.e., from take-off from vaulting table to landing) [ 21 , 34 , 35 ]. The elite group may have more difficulty during these phases of movement, resulting in a reduction in time directing gaze to the mini-trampoline during the approach run, in order to find their hand placement location on the vaulting table.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation